Estudio para el uso y distribución adecuada del Recurso Hídrico presente en la Subcuenca del Río Aláquez del Cantón Latacunga “Mediante Teledetección - Aleaga Cobos, Rubén Andrés (2017)
The project is based on geographic information systems through remote sensing, the researcher studies the water surface in Latacunga Canton at Alquez River, whose purpose is to create a gauging point, superior to 3000 m.s.n.m. in one of its intercessions in order to calculate the volume in cubic meters that would generate the set point, satellite and vectorial images of the canton are downloaded, the arctoolbox tools reclassified by DEM for general maximum, average and minimum levels. Once, these dimensions are established, the morphometric properties of the canton are extracted with spatial analyst tools and sub-basin profile to achieve a mirror delimitation to create points of origin and a destination point. The Thornthwaite formula to calculate the monthly evapotranspiration was used and the crop coefficients for their life cycle were added as well in order to determine a number in cubic meters of the consumptive use of water for agriculture, taking as reference the crops such as potatoes, corn, beans, onions, carrots. In the study, the volume generated by the reservoir is 338554,587 m3, with the crops consumptive use from 8 to 12% that would be used from the reservoir.